Service Learning: A Philosophy and Practice to Reframe Higher Education - Luigina Mortari; Marco Ubbiali (Athens Institute for Education and Research, 2021)
In order to answer the call of Agenda 2030 (UN, 2015), higher education must assist in giving form to a new society in which democracy is cultivated in both the minds and practices of our society. A democratic education is the answer to the challenges of contemporary society, which is characterized by indifference and an unwillingness to engage for the common good. Educational practices are often aligned to this trend so that they are planned with the aim of developing competences useful for individual success and the economic improvement of society. It is necessary to envision a new design for higher education that promotes in people the disposition to engage in the construction of a society where everyone has an equal opportunity to live a good and fulfilling life. Useful for this purpose can be a rediscovery of the classical position of Plato, Socrates, and Aristotle that present virtue and ethics as a theoretical framework for education. This framework can be used as a foundation upon which to renew academic practices by planning and designing experiences able to translate theory into actions. Service learning is an interesting model that would allow for this and would guide practices that support a democratic education informed by virtue and ethics. If useful for redirecting higher education, service learning is particularly suitable for educating teachers, the practitioners who have a great responsibility for transforming society through education. In this paper, after developing the appropriate theoretical framework, we present, as an example of service learning, the Community Research Service Learning experience carried out at the University of Verona in the Primary Teacher Education master's degree program.